216k views
3 votes
If g(x) = -3x^2 +4x+5 find g(3)

User Dima Pasko
by
4.9k points

2 Answers

6 votes

Answer:

g(3) = -10

Explanation:

g(x) = -3x^2 + 4x + 5

g(3) = -3(3^2) + 4(3) + 5

g(3) = -3(9) + 12 + 5

g(3) = -27 + 12 + 5

g(3) = -15 + 5

g(3) = -10

User Istvano
by
5.3k points
2 votes

Answer:

-10

Explanation:

g(x) = -3x^2 +4x+5

Let x = 3

g(3) = -3*(3)^2 +4*3+5

= -3*9 +12+5

= -27+12+5

= -10

User Vojtam
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.